Oral rehydration with a plantain fluor-based solution in children dehydrated by acute diarrhea: A clinical trial (1997)
ABSTRACT: A clinical trial was conducted in order to prove the efficacy of a solution containing 50 g/1 of plantain flour and 3. 5 g/1 of sodium chloride (NaCl) for the rehydration of children with acute diarrheal diseases. 121 children were given WHO-ORS (Group A) and 117 a plantain flour-based solution (Group B). Rehydration was successful in 85. 9% in Group A and 88. 0% in Group B (p= 0. 634). Rehydration was completed in 5. 28 h (SD 1. 99) in Group A and in 4. 88 h (SD 2. 11) in Group B (p= 0. 132). The average solution intake for rehydration was 24. 56ml/kg/h (SD 10. 12) in Group A and 21. 17ml/kg/h (SD 9. 35) in Group B (p= 0. 00782). The mean stool output during rehydration was 8. 45g/kg/h (SD 9. 72) in Group A and 4. 69 g/kg/h (SD 4. 98) in Group B (p= 0. 00053). Decrease in blood levels of sodium and potassium occurred in some children in group B. The plantain flour-based solution proved effective for the treatment of dehydration due to acute diarrheal diseases and should be considered as an alternative when standard WHO-ORS is not available.